Multidimensional health status and its impact on health care consumption behavior among elderly people with chronic diseases: evidence from CHARLS in China - Wang, Qi; Zhang, Yuanyuan; Miao, Xin; Chen, Jinao; Zhang, Linlin (Frontiers in Psychology, 2025)
PurposeThis study aims to provide a comprehensive understanding of the multidimensional health status of elderly individuals with chronic diseases in China and examine its impact on their healthcare consumption behavior.MethodsA chi-square test was conducted to assess the variations in healthcare consumption behavior across different multidimensional health categories. Additionally, a logistic regression model was employed to identify the key determinants influencing healthcare consumption among elderly individuals with chronic diseases from a multidimensional health perspective.ResultsThe chi-square test results indicated a statistically significant association between multidimensional health and healthcare consumption behavior (p < 0.05). Furthermore, the logistic regression analysis identified dyslipidemia, regular participation in social activities, and children’s financial support (≥¥5,801 yuan per year) as significant contributors to healthcare consumption behavior among elderly individuals with chronic conditions (p < 0.05).ConclusionThe findings of this study suggest that both physical and social health play a positive role in enhancing healthcare consumption behavior among elderly individuals with chronic diseases (p < 0.05). These results highlight the importance of targeted policy interventions that integrate physical health management and social engagement strategies to improve healthcare accessibility and utilization in this population.